Making cities of tomorrow more inclusive: evaluating the adequacy of City of Johannesburg’s fiscal tools in realising SDG 11 - Ngobeni, Mokgadi Sophie (My University, 2020)
South African cities are faced with issues of poverty, inequality, climate change and resilience emanating from the past spatial imbalances caused by apartheid. In response to these issues, the country has ascribed to the implementation of Sustainable Development Goals (SDGs) whose success can only be realised at municipal level. The capacity of municipalities is highly reliant on finance which is often not given attention in spatial planning. Insufficient funding for capital projects slows down the delivery of services to communities, impacting negatively on their standard of living. The City of Johannesburg Metropolitan Municipality (CoJMM) is one of the leading municipalities in South Africa experiencing an alarming rate on housing and job mismatch as a result of spatial inequality which is to be addressed by the 2030 Spatial Development Framework (SDF). However, this has an impact on the municipality's budget for the provision of basic infrastructure and services. This study aims to understand the nature and extent of funding for SDG11 in the CoJMM with a focus on inclusive cities. Furthermore, we explore the challenges faced by the municipality in implementing the goal of an inclusive city. A qualitative research method will be employed for this study. Documents analysis will be used to collect information supported by semi-structured interviews through a purposeful sampling of participants from the government as well as NGOs who have an understanding of the municipal finance as well as fiscal tools enabling the municipality to deliver services. This study expects to find that the CoJMM’s fiscal capacity is dependent on the priority policy mandate from the national government
A research report submitted to the faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Science in Development Planning, 2020
Keywords: SDG-11: Sustainable cities and communities